Improvement of least squares integration method with iterative compensation for shape reconstruction from gradient - Huang, Lei (2013)
An improvement is made to the traditional 2D integration with least squares method by introducing an iterative compensation procedure. The issue of inaccurate reconstruction due to imperfection of Southwell grid model is solved through the introduced iterative compensations. The feasibility and superiority of the proposed method are investigated with simulations. Moreover, the proposed method is compared with the integration method with radial basis functions.